The effect of military actions on the dynamics of the use of agricultural land and the state of the soil cover - Bogdanets, V.; Nosenko, V.; Mizerna, N.; Nosylia, A. (Land Management, Cadastre and Land Monitoring, 2023)
The topicality of the topic is due to significant changes in the state of the components of the environment, namely the soil cover, and the use of agricultural land under the influence of the consequences of military operations in 2022-2023. There is a need to assess the scale of changes in the environment, primarily the soil cover, as the most disturbed as a result of hostilities, under the influence of these factors, to determine their respective scales, spatial localization and ecological and legal consequences. The main negative factors that lead to damage to agricultural land include (according to Kondratenko A.F. 2022): 1. Driving through the territory of heavy equipment (tanks and other types of tracked equipment, which leads to soil compaction and degradation); 2. The use of anti-tank and anti-personnel mines, which leads to changes in landscapes, relief and soil degradation; 3. Shelling and bombing of the territory, which leads to the formation of craters (funnels) and mixing of soil horizons. Sinkholes in places where shells fall are not only a factor of landscape damage and destruction of vegetation, but also a factor of soil pollution: they leave in the soil a significant amount of metal, sulfur and sulfur compounds, heavy metals, ammonia, phosphorus, coal dust, sulfuric acid and sulfate compounds, formaldehydes, lead, mercury; 4. Construction of trenches and other protective shelters for military personnel and equipment (soil disturbance and degradation); 5. Fires in natural areas and agricultural fields. As a result, the fertile soil layer burns out, dehydration and "sterilization" occurs - both pathogenic microorganisms and useful biota die, nutrients are lost. In our opinion, this classification generally covers well the spectrum of factors affecting the soil cover of military operations. At the same time, this classification is incomplete and does not cover some common cases, for example, the creation of systems of defensive structures leads to the violation of soil horizons and changes in the structure of the soil, the spread of erosion (Makarenko N. A., et al., 2022). Also, since it was developed for the conditions of military operations in Donetsk region as of 2014-2017, it needs to be supplemented and clarified, for example, it is worth adding the concepts of ecocide and destruction of infrastructure. The use of indicators of soil condition, monitoring of the development of degradation processes based on operational data and the possibility of using geoportals, dashboards and other means of public access to open data plays a particularly important role in the context of the impact of the consequences of military actions on the soil cover, prospects for agricultural production and, in general, on the quality of life. Key words: agricultural lands, soil cover, soil degradation, dynamics of land use, military operations.